(untitled) (Biological Sciences - PJSIR, 2005)
Secondary metabolites were induced in carrot tissues on treatment with high molecular weight crude elicitor “polysaccharides” preparations (HMWCEPs) from red algae, Hypnea musciformis, Acanthophora delili and Botryocladia leptopoda collected from the coast of Karachi, Pakistan. A simple microtechnique based on UV-visible spectrophotom- etry is described for the quantification of induced secondary metabolites as a function of time and doses of elicitor preparations.